ENGARUH KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR PESERTA DIDIK KELAS XI MIPA 1 DI SMA NEGERI 2 RANTAU SELATAN KABUPATEN LABUHANBATU - PUTRI, DESI MELINDA; Megawati, Betti; ulya, basyarul (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
This research aims to to determine the Influence of Emotional Intelligence on the Learning Achievement of Class XI MIPA 1 Students at SMA Negeri 2 Rantau Selatan, both through Tests and Non-Tests. The population in this study were Class XI Mas Al Washliyah Marbau Students, the research time was from March to May 2024 whose number could not be determined. Determination of the number of samples using the Arikunto formula with a total of 35 people and the analysis method used was the Test analysis method, Test Validity Test, Reliability, and Hypothesis Testing. The results of partial hypothesis testing (t-test) showed that Emotional Intelligence had a significant effect on the Learning Achievement of Class XI MIPA 1 Students at SMA Negeri 2 Rantau Selatan. The results of the hypothesis test obtained that t count <t table, namely 3.329 <1.689, then H0 was rejected and Ha was accepted, so there was a significant influence between Emotional Intelligence on the Learning Achievement of Class XI MIPA 1 Students at SMA Negeri 2 Rantau Selatan.